Bone mineral loss in young women with amenorrhoea. Issue 6755 (6th October 1990) - Davies, M C; Hall, M L; Jacobs, H S
Abstract : OBJECTIVE--To examine the impact of amenorrhoea on bone mineral density in women of reproductive age. DESIGN--Cross sectional study of 200 amenorrhoeic women compared with normally menstruating controls. SETTING--Teaching hospital outpatient clinic specialising in reproductive medicine. SUBJECTS--200 Women aged 16-40 with a past or current history of amenorrhoea from various causes and of a median duration of three years, and a control group of 57 age matched normal volunteers with no history of menstrual disorder. MAIN OUTCOME MEASURE--Bone mineral density in the lumbar spine (L1-L4) as measured by dual energy x ray absorptiometry. RESULTS--The amenorrhoeic group showed a mean reduction in bone mineral density of 15% (95% confidence interval 12% to 18%) as compared with controls (mean bone mineral density 0.89 (SD 0.12) g/cm2 v 1.05 (0.09) g/cm2 in controls). Bone loss was related to the duration of amenorrhoea and the severity of oestrogen deficiency rather than to the underlying diagnosis. Patients with a history of fracture had significantly lower bone density than those without a history of fracture. Ten patients had suffered an apparently atraumatic fracture. CONCLUSIONS--Amenorrhoea in young women should be investigated and treated to prevent bone mineral loss. Menopausal women with a past history of amenorrhoea should be considered to be at high risk of osteoporosis.